B randing development tendency in Kazakhstan and ways to resolve the problems. - Bagdatov, S. A.; Nizamova, N. A. (Journal of Economic Research & Business Administration, 2015)
Having considered the application of branding industry author came to the conclusion that the practice and theory of branding in Kazakhstan is poorly developed and poorly explored. For possession of an advantage over competitors in a market economy, we should not forget about the need for branding. The author thinks that in Kazakhstan there are many restrictions for the development of branding, which should be revie wed.